Undrained deformation characteristic of saturated soft clay under traffic loading - Lei SUN; Yuke WANG (Shuiwen dizhi gongcheng dizhi)
Previous studies on the undrained deformation behavior of saturated soft clay under traffic loading usually ignored the effect of cyclic confining pressure. In the present study, a series of undrained constant confining pressure (CCP) and variable confining pressure (VCP) cyclic triaxial tests were conducted on Wenzhou soft clay through GDS cyclic triaxial test system to investigate the deformation behavior of saturated soft clay subgrade under different stress paths due to traffic loading. Special attention was paid to the effects of cyclic stress ratio (CSR) and stress path (α) on the dynamic resilient modulus as well as axial accumulated strain. The test results show that under undrained conditions, the dynamic resilient modulus decreases with the increase of CSR and α, while the axial accumulated strain increases with the increase of CSR and α. It suggests that cyclic confining pressure can improve the stiffness and restrain the axial strain accumulation of saturated soft clay under cyclic loading. Based on the test results and the existing empirical models, a dynamic resilient modulus empirical model and an axial strain accumulation model were established, respectively, which consider the influence of stress paths due to traffic loading, and can be used to calculate and analyze the long-term deformation of soft clay soil foundation under traffic loading.